THE ESSENCE OF CLT OF TEACHING FOREIGN LANGUAGES (International journal of artificial intelligence, 2025)
In the ever-evolving landscape of language education, various teaching methods have come and gone, each attempting to address the challenges and nuances of learning a new language. One of the most significant and widely adopted approaches is Communicative Language Teaching (CLT). Emerging in the 1970s, CLT revolutionized the way foreign languages were taught by shifting the focus from traditional grammar-based instruction to an emphasis on communication and real-world language use. This shift reflects a fundamental change in how language learning is viewed, with CLT prioritizing fluency over mere accuracy and emphasizing functional language use. This article explores the essence of CLT, its principles, key features, and how it has shaped modern foreign language teaching. By understanding the core concepts of CLT, educators can better appreciate its potential to improve language learners’ communicative competence and overall language proficiency.